2021
DOI: 10.9734/jpri/2021/v33i35b31919
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Mass Index and Skin Fold Thickness in Young Females

Abstract: Background: Anthropometric indicators are used to evaluate the prognosis of chronic and acute diseases, and to guide medical intervention. In anthropometry, body mass index (BMI) is widely accepted in determining obesity and skin fold thickness measurements provide good estimates of body fat. Aim: To see the relationship between BMI and skin fold thickness in young females. Study Design: Observational study Methodology: This was a cross-sectional study. Measurements of height, weight, BMI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…4 and 5 shows two causal relationships with a change in direction: and . Between them, indicates that the change in BMI results in a change in the skin fold thickness of triceps (subcutaneous fat thickness).Studies have shown [ 32 , 33 ] that there is a significant correlation between the thickness of the triceps skin fold and BMI. When the BMI value increases, the weight change increases, and the subcutaneous fat thickness increases, so the causality is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 5 shows two causal relationships with a change in direction: and . Between them, indicates that the change in BMI results in a change in the skin fold thickness of triceps (subcutaneous fat thickness).Studies have shown [ 32 , 33 ] that there is a significant correlation between the thickness of the triceps skin fold and BMI. When the BMI value increases, the weight change increases, and the subcutaneous fat thickness increases, so the causality is reasonable.…”
Section: Discussionmentioning
confidence: 99%